The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2147/dmso.s40840
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of metformin, resveratrol, and hydroxymethylbutyrate on insulin sensitivity

Abstract: BackgroundThe purpose of this study was to determine whether a mixture of the polyphenol, resveratrol, and the leucine metabolite, hydroxymethylbutyrate (HMB), acts synergistically with low doses of metformin to impact insulin sensitivity and AMP-activated protein kinase-dependent outcomes in cell culture and in diabetic mice.MethodsC2C12 skeletal myotubes and 3T3-L1 adipocytes were treated with resveratrol 0.2 μM, HMB 5 μM, and metformin 0.1 mM alone or in combination. db/db mice were treated for 2 weeks with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 40 publications
(45 reference statements)
2
20
0
Order By: Relevance
“…This may be attributed to their combined antihyperglycemic, anti-oxidant and antiinflammatory properties together with their ability to affect TGF-β1 and advanced glycation end products together with induction of apoptosis. This was in agreement with Bruckbauer and Zemel [33] who reported that resveratrol combined with metformin may act synergistically on AMP-activated protein kinase-dependent pathways, leading to increased insulin sensitivity, which in turn may reduce the therapeutic doses of metformin needed for treatment of diabetes and may ameliorate its complications including DN. Moreover, Movahed et al [34] found that the antihyperglycemic effect of resveratrol had an additive effect when combined with metformin in treatment of type-2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 91%
“…This may be attributed to their combined antihyperglycemic, anti-oxidant and antiinflammatory properties together with their ability to affect TGF-β1 and advanced glycation end products together with induction of apoptosis. This was in agreement with Bruckbauer and Zemel [33] who reported that resveratrol combined with metformin may act synergistically on AMP-activated protein kinase-dependent pathways, leading to increased insulin sensitivity, which in turn may reduce the therapeutic doses of metformin needed for treatment of diabetes and may ameliorate its complications including DN. Moreover, Movahed et al [34] found that the antihyperglycemic effect of resveratrol had an additive effect when combined with metformin in treatment of type-2 diabetes mellitus.…”
Section: Discussionsupporting
confidence: 91%
“…Clinically, metformin acting as one of the antidiabetic drugs, has been shown to effectively prevent against diabetes and related complications. The pharmacological action of metformin is primarily involved in enhancing insulin sensitivity and increasing peripheral glucose uptake, thereby reducing hyperglycemia and metabolic disturbance [29]. Therefore, this study indicated that for diabetes patients, metformin treatment and EACR supplement may contribute to diabetes management, and may yield additional benefits through combined administration.…”
Section: Discussionmentioning
confidence: 92%
“…RSV has been the subject of intense scientific and public interest in recent years, mainly due to its widely reported ability to delay ageing and prevent age-related diseases [23,24,25]. The beneficial effects of RSV were originally thought to derive from its antioxidant properties [26].…”
Section: Discussionmentioning
confidence: 99%